Resource-Financed Infrastructure: Thoughts on Four Chinese-Financed Projects in Uganda - Tom, Ogwang; Frank, Vanclay (MDPI AG, 2021)
Increasingly common methods for financing public infrastructure in developing economies are Resources-for-Infrastructure (R4I) and Resource-Financed Infrastructure (RFI), usually involving Chinese financial institutions and Chinese construction companies. Although there are advantages to the borrowing country from these project financing arrangements, there are also various issues and governance challenges. In Uganda, expectations around future revenue from oil extraction have led to many infrastructure projects being commissioned, mostly funded by RFI arrangements. To consider the appropriateness of these arrangements and to reflect on whether they are likely to contribute to positive development outcomes or be examples of the resource curse, we examined four public infrastructure projects: Kampala–Entebbe Expressway; Karuma Hydroelectric Dam; Isimba Hydroelectric Dam; and the Malaba to Kampala section of the East Africa Standard Gauge Railway. Although R4I/RFI arrangements are viewed positively by some commentators, others (especially local companies) consider they lack transparency, create unsustainable debt, promote China’s interests over the borrowing country, increase unemployment, unfairly compete with local business, deal in corruption, have poor working conditions, and result in substandard construction. Nevertheless, we conclude that Uganda and other developing countries have generally benefited from Chinese-funded infrastructure, and there is more myth trap than debt trap. However, to ensure positive development outcomes, governments and construction companies should ensure compliance with international standards, especially relating to: environmental and social impact assessment; human rights; benefit-sharing arrangements; livelihood restoration; and project-induced displacement and resettlement.
Keywords: China in Africa; China Exim Bank; international development finance; megaprojects; elite capture; extractive industries and society; environmental; social and governance issues; resource governance; Nigerian disease; China Belt and Road Initiative